Development of a primary standard for absorbed dose from unsealed radionuclide solutions. (19th October 2016) - Billas, I; Shipley, D; Galer, S; Bass, G; Sander, T; Fenwick, A; Smyth, V
Abstract: Currently, the determination of the internal absorbed dose to tissue from an administered radionuclide solution relies on Monte Carlo (MC) calculations based on published nuclear decay data, such as emission probabilities and energies. In order to validate these methods with measurements, it is necessary to achieve the required traceability of the internal absorbed dose measurements of a radionuclide solution to a primary standard of absorbed dose. The purpose of this work was to develop a suitable primary standard. A comparison between measurements and calculations of absorbed dose allows the validation of the internal radiation dose assessment methods. The absorbed dose from an yttrium-90 chloride ( 90 YCl) solution was measured with an extrapolation chamber. A phantom was developed at the National Physical Laboratory (NPL), the UK's National Measurement Institute, to position the extrapolation chamber as closely as possible to the surface of the solution. The performance of the extrapolation chamber was characterised and a full uncertainty budget for the absorbed dose determination was obtained. Absorbed dose to air in the collecting volume of the chamber was converted to absorbed dose at the centre of the radionuclide solution by applying a MC calculated correction factor. This allowed a direct comparison of the analytically calculated and experimentally determined absorbed dose of an 90 YCl solution. The relative standard uncertainty in the measurement of absorbed dose at the centre of an 90 YCl solution with the extrapolation chamber was found to be 1.6% ( k = 1). The calculated 90 Y absorbed doses from published medical internal radiation dose (MIRD) and radiation dose assessment resource (RADAR) data agreed with measurements to within 1.5% and 1.4%, respectively. This study has shown that it is feasible to use an extrapolation chamber for performing primary standard absorbed dose measurements of an unsealed radionuclide solution. Internal radiation dose assessment methods based on MIRD and RADAR data for 90 Y have been validated with experimental absorbed dose determination and they agree within the stated expanded uncertainty ( k = 2).